Biomarkers of oxidation, inflammation and intestinal permeability in persons with diabetes mellitus with parenteral nutrition: A multicenter randomized trial - Soria-Utrilla, Virginia; Sasso, Corina Verónica; Romero-Zerbo, Silvana Yanina; Adarve-Castro, Antonio; López-Urdiales, Rafael; Herranz-Antolín, Sandra; García-Almeida, José Manuel; García-Malpartida, Katherine; Ferrer-Gómez, Mercedes; Moreno-Borreguero, Alicia; Luengo-Pérez, Luis Miguel; Álvarez-Hernández, Julia; et al. (Elsevier, 2025)
Background and aims: Parenteral nutrition (PN) composition could play a role in the management of systemic inflammatory response and intestinal barrier disruption. We aimed to evaluate changes in biomarkers of inflammation, oxidative status and intestinal permeability in patients with type 2 diabetes mellitus (T2DM) who received different PN lipid formulas. Methods: This was a prospective study, including 94 patients with T2DM who received omega (n)-3 polyunsaturated fatty acids (PUFA)-enriched PN, a mixture of medium and long chain triglycerides (MCT/ LCT) PN, or an olive oil-based PN. Serum levels of biomarkers of oxidative status, intestinal permeability and inflammation biomarkers were determined at day 1 and day 5 after PN initiation. Registered under ClinicalTrials.gov Identifier no. NCT02706119.

Results: At day 5 after the onset of PN, the MCT/LCT group had a significant reduction of 2 proinflammatory cytokines [interleukin (IL)-15, IL-17A], elevation of the anti-inflammatory cytokine IL-13 and increase of zonulin and indoxylsulfate. The olive oil group showed a statistically significant reduction of 5 proinflammatory cytokines [IL-1b, IL-17A, IL-6, cytokine-leukemia inhibitory factor (LIF) and tumor necrosis factor alpha (TNF-a)] and reduced concentrations of the anti-inflammatory cytokine IL-1RA, while the n-3 PUFA-enriched group presented a statistically significant reduction of 8 proinflammatory cytokines (interferon-gamma, IL-1b, IL-15, IL-17A, IL-6, LIF, monocyte chemoattractant protein 1, and TNF-a). In the between-group comparisons, indoxylsulfate significantly increased in the MCT/LCT group compared to the n-3 PUFA-enriched group, while 8-isoprostane and indoxylsulfate significantly increased in the MCT/LCT group compared to the other groups and superoxide dismutase significantly decreased in the MCT/LCT group compared to the other groups. Conclusion: In patients with T2DM, PN lipid composition exerts a profound impact on proinflammatory, prooxidative and intestinal permeability biomarkers
Keywords: Alimentación parenteral; Inflamación (Patología); Intestinos; Diabetes tipo 2; Inflammation; Intestinal permeability; Oxidative status; Parenteral nutrition